Influence of Technological Maturity on the Secondary Metabolites of Hemp Concentrate (Cannabis sativa L.) - Bohuslava Tremlová; Hana Koudelková Mikulášková; Klaudia Hajduchová; Simona Jancikova; Dominika Kaczorová; Sanja Ćavar Zeljković; Dani Dordevic (Foods, 2021)
During the last decade, the popularity of hemp products has been rising rapidly. Products containing cannabidiol (CBD) are of predominant interest. Traditional hemp products are frequently enriched by CBD due to their potential therapeutic effects. Cannabidiol occurs naturally in hemp juice together with other biologically active substances, such as terpenes, flavonoids, and stilbenoids. These constituents act synergistically. This study aimed to observe the influence of the hemp plant developmental stage on its chemical composition and antioxidant activity. The hemp plants were analyzed during three vegetative stages, i.e., before, during, and after flowering. The collected samples were evaluated using the following analyses: total polyphenolic content and profile, terpenoid and cannabinoid contents, and ferric reducing antioxidant power. The results revealed statistically significant differences between the samples in almost all set parameters. The optimal period for hemp harvest depends on desirable compounds, i.e., phenolic content is the highest before flowering, while the levels of cannabinoids and terpenoids are the highest during the flowering period.